2014
DOI: 10.1007/s13277-014-2096-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of caspase9 promoter polymorphisms with the susceptibility of AML in south Indian subjects

Abstract: Abnormal apoptosis is one of the hallmarks of cancers including acute myeloid leukemia (AML), as it plays a pivotal role in precisely maintaining self-renewal, proliferation, and differentiation properties of hematopoietic stem cells (HSCs). Caspase9 (CASP9), an initiator caspase activated by mitochondrial-mediated apoptotic pathway (intrinsic pathway), triggers cascade of effector caspases and executes apoptosis. Functional SNPs in CASP9 might influence the gene expression leading to altered apoptosis which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 41 publications
1
16
1
Order By: Relevance
“…CASP9 , an important initiator CASP of the intrinsic pathway, is activated by the release of cytochrome c from mitochondria, activates downstream the effector CASP3 and CASP7 [2223]. Many previous studies have shown that polymorphisms in CASP9 were associated with various cancer types, especially in the promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…CASP9 , an important initiator CASP of the intrinsic pathway, is activated by the release of cytochrome c from mitochondria, activates downstream the effector CASP3 and CASP7 [2223]. Many previous studies have shown that polymorphisms in CASP9 were associated with various cancer types, especially in the promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…Even greater challenges relate to understanding noncoding CASP9 polymorphisms associated with hematopoietic malignancies (Hosgood et al, 2008;Lan et al, 2009;Kelly et al, 2010;Cingeetham et al, 2014), new-onset diabetes after renal transplant (McCaughan et al, 2014), and treatment efficacy for Crohn's disease (Hlavaty et al, 2005;Ferreira et al, 2010;Cravo et al, 2014). Biochemical analysis of patient samples can help identify if these noncoding variants are correlated with alterations in caspase-9 activity or expression in disease-relevant tissues.…”
Section: Genetics Of Caspase-9 In Human Diseasementioning
confidence: 99%
“…5) [17]. Table 2 (Supplementary 1) shows a small chunk of mutation analysis data produced from the ongoing study.…”
Section: Mdr Analysesmentioning
confidence: 99%